Physical and mathematical model tribosystem «working tool - land» - Дворук, В.І.; Борак, К.В. (Problems of Tribology, 2016)
The results of physical and mathematical modeling tribosystem "working tool – land". The processes that occur in a dynamic state in tribosystem and objectives for further research.